Performance And Exhaust Emission Of Spark Ignition Engine On Various Spark Plug Gap - Feri Hidayatulloh; Ata Nugraha (Automotive Innovations Journal, 2026)
Spark plugs are components that play an important role in the ignition system of internal combustion engines. In this study, three spark plug gaps have been varied to investigate the combustion process in the combustion chamber by evaluating engine performance and exhaust emissions. The type of engine used for testing is a 1 cylinder 4 stroke engine with a capacity of 125cc using RON 90 fuel. The variations in spark plug electrode gaps applied are 0.4, 0.6 and 0.8 mm. Engine performance and emission levels were tested using a Rextro pro-dyno dynamometer and a techno test gas analyzer. Several main parameters of engine performance such as torque, power and fuel consumption were observed in three different variations and exhaust gases such as CO, CO2, HC and O2 were also observed. The results showed that engine performance increased. The highest increase in engine performance was at a spark plug gap of 0.8 mm compared to other spark plug gap variations. The resulting exhaust emissions increased in all spark plug gap parameters. Maximum power is achieved at 6.86 kW and maximum torque is 8.86 Nm at a spark plug gap of 0.8 mm. Low exhaust emissions are produced at a spark plug gap of 0.4 mm